Post-Covid Indigenous Women Entrepreneurship: A Case of the Kichwa-Puruha in Ecuador - Saiz-Alvarez, J (IGI Global, 2021)
Despite its great importance within the indigenous communities of Ecuador, the number of studies carried out on the Kichwa (Quichua)-Puruha indigenous population is minimal: the majority of those that have been undertaken are related to archaeological issues. The purpose of this chapter is to shed light on the socioeconomic and cultural traits of female entrepreneurship in the Kichwa (Quichua)- Puruha indigenous group and how this relates to the Sumak Kawsay (Harmonious Life) in the region of Chimborazo, one of the most impoverished provinces of Ecuador. In order to achieve this goal, a mixed methodology has been applied made up of focus groups, in-depth interviews, questionnaires, and hours of direct observation. The results show that indigenous female entrepreneurs belonging to the Kichwa (Quichua)-Puruha ethnic group living in the Chimborazo region are guided by four concepts-relationship, correspondence, reciprocity, and complementarity-and on five principles related to national culture and which are related to sustainable development. © 2021, IGI Global.